Performance and Complexity Analysis of MAC Protocol for VANETs - Shah, A. F. M. Shahen; Ilhan, Haci; Tureli, Ufuk (IEEE, 2019)
The IEEE 802.11 outlined the MAC layer specification for vehicular ad hoc networks (VANETs). In this paper, to assess the performance of the IEEE 802.11 medium access control (MAC) for VANETs, an analytical model based on Markov chain model is presented. The parameters that could impact performance such as number of vehicles, velocity, vehicle density, contention window (CW) size, packet size, transmission range etc. are considered. The relationship among parameters and performance metrics are derived. The probability of successful transmission, throughput, and delay expressions are obtained. Complexity analysis is presented. Furthermore, to verify the analytical studies numerical results are demonstrated and whether the IEEE 802.11 can fulfill the performance criteria for VANETs or not is checked.
Keywords: Complexity; IEEE 802.11; MAC; Markov chain model; safety messages; non-safety data; VANETs; IEEE-802.11 DCF; Computer Science; Engineering; Telecommunications